Perspectives on what is needed to implement genomic medicine. Issue 3 (6th March 2015) - Williams, Marc S.
<x xml:space="preserve">Abstract</x> This commentary briefly explores some of the additional factors needed to incorporate genomics into clinical care including the role of electronic health records, measuring the value of interventions and implementation science. Distinctions between genomic, personalized and precision medicine will be examined.